(untitled) (Bangladesh Critical Care Journal, 2023)
Among endocrine emergencies thyroid storm is a very devastating disease. Sometimes patient presents with cardiovascular or neurological disorder, admits in general medical unit other than ICU. But all Thyroid storm patients should be treated in medical ICU. Delay in diagnosis and/or treatment increases morbidity and mortality. Presentation usually with severe hyperthyroid with other systemic dysfunction. Liver function test usually altered. It has got definite diagnostic criteria. Burch HB, Wartofsky L has a scoring scale. Temperature, involvement of central nervous system, Gastro-intestinal or Liver, Heart rate, Atrial fibrillation and precipitating factors give definite scoring system and ideas for prognosis. Treatments depend on severity and associated co-morbidities. Propylthiouracil or Carbimazole or Methimazole should be started early. Propranolol/beta blocker, Digoxin, Saturated Solutions of Potassium Iodide, Hydrocortisone, Antibiotics and IV fluids are essential. Rarely treated with Cholestyramine, Lithium etc. Plasmapheresis is a lifesaving procedure. Bangladesh Crit Care J September 2023; 11 (2): 121-126